Health Promotion and Diseases Prevention Model for Non Communicable Diseases among Risk Group, Nan Province - ศิริ, นิยม; นาคอ้าย, วรยุทธ (Journal of Health Science of Thailand, 2022)
This qualitative study was aimed to synthesize a health promotion and prevention model for risk people with noncommunicable diseases (NCDs): diabetic mellitus and hypertension, and to study the key success that support operation factors. Data were collected through participated observation, field note and in-depth interviews from 16 key informants recruited from snowball purposive sampling. They were health workers, community health volunteers, family health volunteers, and people at risk of NCDs. The data were analyzed by content analysis. The research result showed that a health promotion and prevention model for non-chronic communicable diseases among the risk people consisted of 5 components which were interrelated in a circular pattern. The inner circle was a health literacy development process; the outer circle represented participating network; and the third circle was the network’s roles which was surrounded by the fourth circle representing the network’s core competencies. The outermost circle was for supportive agencies that provided assistance with policy and budgets. The key performances for the success were the NCDs policy implementation through district health committees’s process, network’s participation and community strengthening.